LEWIS-BASE ADDUCTS OF LEAD(II) COMPOUNDS VI.* SYNTHESIS AND STRUCTURAL CHARACTERIZATION OF MONONUCLEAR (DIACETATO-0,O ')(1, 10-PHENANTHROLINE) (Journal of Sciences, Islamic Republic of Iran)
The synthesis and single-crystal X-ray structure determination of the title compound (phen)Pb(02CMe) is described. The complex crystallizes in the monoclinic space group P2 /c, a = 7.823(3), b = 12.421(4), c = 9.262(2) ?, ? = 79.92(3)", Z = 4, yielding R 0.048 for 3210 independent reflections. The coordination number around the lead atom is six. [Pb-N 2.54(2), 2.56(4)],[Pb-0, 2.19-2.22]